Shield privacy: A conceptual framework for information privacy and data access controls - Skinner, Geoffrey; Han, Song; Chang, Elizabeth (WSEAS Press, 2006)
With the increasing number of proposals and approaches to privacy protection, it has become very difficult to build information systems that provide comprehensive protection for a very broad range of information privacy issues. Proposals to information privacy are normally based on one or a combination of the four major models of privacy protection. That is, Comprehensive Privacy Laws, Sectoral Privacy Laws, Privacy Self-Regulation, and Technologies of Privacy. Used without direction or by not following privacy by design principles results in the ineffective privacy protection. What is required is a complete solution, that gives due consideration to all models, and is easily integrated in to all types of environments. In this paper we address this problem by providing a privacy solution for integration into information systems called Shield Privacy. The Shield Privacy solution provides an effective system wide approach to privacy protection. It integrates relevant components from the various privacy models while also providing comprehensive information security through privacy influences data access controls.